THE INFLUENCE OF WELDING ENGINEERING TEACHER COMPETENCE TEST TRAINING AND EDUCATION TOWARD THE QUALITY OF TEACHERS AT VOCATIONAL TECHNOLOGY TRAINING AND EDUCATIONAL INSTITUTION SOUTH SULAWESI PROVINCE - Ma’ruf (Media Inovasi Pendidikan dan Publikasi, 2023)
The aim of this research was to find out and analyze the influence of welding engineering teacher competence test training and education toward the quality of teachers at vocational technology training and educational institution South Sulawesi Province. This research employed primary data in which the questionnaire answers from teacher respondents were analyzed using double linear regression with SPSS 20 program. The samples were 40 teacher respondents who had followed training and education of competence test conducted at vocational technology training and educational institution South Sulawesi Province. Based on the result of the research analysis, it was shown that welding engineering teacher competence test training and education had influenced toward the quality of the teachers at vocational technology training and educational institution, South Sulawesi Province. Therefore, this research concluded that if there is an increase frequency of teacher training and education of competence test, then ideally, there should be also an increase of teacher’s quality competence.